Lifespan in rodents with MYT1L heterozygous mutation - Allyson Schreiber; Raylynn G. Swift; Leslie Wilson; Kristen L. Kroll; Joseph D. Dougherty; Susan E. Maloney (Scientific Reports)
Abstract MYT1L syndrome is a newly recognized disorder characterized by intellectual disability, speech and motor delay, neuroendocrine disruptions, ADHD, and autism. In order to study this gene and its association with these phenotypes, our lab recently created a Myt1l heterozygous mutant mouse inspired by a clinically relevant mutation. This model recapitulates several of the physical and neurologic abnormalities seen in humans with MYT1L syndrome, such as weight gain, microcephaly, and behavioral disruptions. The majority of patients with this syndrome are young, and little is known about the impact of age on health and mortality in these patients. Using a Myt1l mutant mouse, we examined the impact of Myt1l mutation on body weights, lifespan, and histopathology findings of mice at the end of life. This cohort of heterozygous mice demonstrated increased body weight across the lifespan, however there was no significant difference in lifespan, apparent cause of death, or end of life histopathological findings between Myt1l heterozygous and wildtype mice. These findings suggest while Myt1l heterozygous mutation may influence overall brain development, it does not strongly impact other organ systems in the body over time.